(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fortification of iron and zinc in jaggery powder can be an effective strategy to increasethe intake of these essential minerals in populations at risk of deficiencies. However, itis important to ensure that the fortified product is safe, effective, and acceptable to thetarget population. The feasibility of fortifying jaggery powder with iron and zinc depends on several factors, including the availability of iron and zinc compounds, the cost of fortification, the stability of the fortified product, and the acceptability of the fortified product to the target population. Jaggery powder, a traditional sweetener derived from sugarcane juice or palm sap, is known for its nutritional value and rich mineral content. Fortification of jaggery powder with iron and zinc has emerged as a potential solution to address these deficiencies. This article explores the feasibility of iron and zinc fortification in jaggery powder, considering various aspects such as availability of fortificants, stability of fortified product, cost implications, and consumer acceptability.